Optimization of passive filter components through active filtering of current ripple reduction in an inverter - Jeyaraman Ramakrishnan; Chengalvarayan Natarajan Ravi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper employs the active input current filtering concept developed and explained to optimize the conventional passive filter components in a two-stage telecommunication inverter. A prototype inverter has been designed for a rated power of 800 W. Optimization of the passive filter components consisting of inductance inductors tank (LTank) and capacitance capacitors tank (CTank) was performed through simulations. The simulation model used for this optimization was validated using the developed prototype. The focus of this work is to limit the input direct current (DC) current ripple within the limits specified in European Telecommunications Standards Institute (ETSI) 300132-2 for a battery supplied telecommunication inverter and optimize the passive filter components. Using the active filtering technique, limit the input current ripple and simultaneously reducing the filter capacity in DC-link. This advantage of active filtering technology over the conventional passive inductors and capacitors (LC) filter concept is explored and demonstrated in this paper.